NURSING COMPETENCY: A CONCEPT ANALYSIS (The Research of Medical Science Review, 2025)
Background: Competency in nursing is a foundational element influencing the quality, safety, and effectiveness of patient care. Despite its central importance, the term remains ambiguously defined across educational, clinical, and policy contexts.Aim: This concept analysis aimed to critically examine the available evidence on nursing competency, identify its defining attributes, and clarify its implications for contemporary nursing practice, education, and policy development.Methods: Walker and Avant’s eight-step concept analysis framework was used to explore and analyze the concept of nursing competency. A total of 10 relevant articles were included following a comprehensive literature review.Results: The analysis revealed that nursing competency is a multifaceted and dynamic concept, encompassing cognitive abilities, technical proficiency, ethical judgment, emotional intelligence, and professional values. Three defining attributes were identified: knowledge, self-assessment, and adaptability. Antecedents included education, skills, and a sense of responsibility, while consequences highlighted improved patient safety, reduced medical errors, and enhanced decision-making. The study emphasized the need for objective and multi-perspective evaluation tools for assessing competency.Conclusion: Nursing competency is essential for delivering high-quality, patient-centered care. This analysis provides a clearer understanding of the concept by identifying its key attributes and implications. The findings support the integration of competency-based frameworks in nursing education, clinical practice, and policy to ensure effective workforce development and optimal patient outcomes.